Beyond the Board: CYBERPOLY as a Multidimensional Gamified Learning Tool for Cybersecurity Awareness - Sakinah Ali Pitchay; Anis Syahira Suhaimi; Farida Hazwani Mohd Ridzuan; Azni Haslizan Ab Halim; Najwa Hayaati Mohd Alwi (Akademia Baru Publishing, 2025)
Indexed